Labor Supply Prediction when Tax Avoidance Matters - Jonas Agell; Mats Persson; Hans Sacklén (Uppsala University, Department of Economics, 1999)
We examine how tax avoidance in the form of trade in well-functioning asset markets affects the empirical study of labor supply. We discuss the implications for tax policy analysis, and we show that a failure to account for avoidance responses may lead to huge errors when predicting how tax reform affects labor supply tax revenue, and the welfare cost of taxation. In conclusion we argue that our model may explain a number of otherwise hard to understand dimensions of tax payer response.
Keywords: H31; J22; 330; Labor supply; tax avoidance; asset markets; tax reform simulation; Arbeitsangebot; Steuervermeidung; Finanzmarkt; Theorie